1999
DOI: 10.1086/306586
|View full text |Cite
|
Sign up to set email alerts
|

Cometary Dust in the Debris Disks of HD 31648 and HD 163296: Two “Baby” β Pictoris Stars

Abstract: The debris disks surrounding the pre-main sequence stars HD 31648 and HD 163296 were observed spectroscopically between 3 and 14 µm. Both possess a silicate emission feature at 10 µm which resembles that of the star β Pictori and those observed in solar system comets. The structure of the band is consistent with a mixture of olivine and pyroxene material, plus an underlying continuum of unspecified origin. The similarity in both size and structure of the silicate band suggests that the material in these system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…Some IDPs (interplanetary dust particles) have similar emissivity curves. This resemblance, which was first noted in β Pic, now extends to many related systems (Sitko et al, 1999).…”
Section: Hd 100546: Mineralogy Of Solids and Possible Cometary Activitysupporting
confidence: 52%
“…Some IDPs (interplanetary dust particles) have similar emissivity curves. This resemblance, which was first noted in β Pic, now extends to many related systems (Sitko et al, 1999).…”
Section: Hd 100546: Mineralogy Of Solids and Possible Cometary Activitysupporting
confidence: 52%
“…Ground-based 10 and 20 µm work on samples of brighter sources (e.g. Hanner et al 1995Hanner et al , 1998Sitko et al 1999;van Boekel et al 2003;Kessler-Silacci et al 2005) and especially ISO 2-30 µm spectroscopy (e.g. Meeus et al 2001;Bouwman et al 2001) have revealed an impressive suite of solid state (and PAH) dust features.…”
Section: The Potential For Planet Formation In Young Circumstellar Disksmentioning
confidence: 99%
“…The optical and UV spectroscopic data, particularly for Ha and Mg II, suggested that HD 163296 should resemble younger Herbig Ae stars such as AB Aur. Studies using IR spectroscopy have begun to probe the chemistry and mineralogy of the disk with detections of warm (r ¹ 30 AU ; van Dishoek et al 1998) and a wealth H 2 of silicate features (Sitko et al 1999 ;van den Ancker et al 2000) resembling cometary materials. In contrast to the optical spectra, the silicate data suggest that the system should resemble more evolved protoplanetary to young planetary disks such as b Pic.…”
Section: Introductionmentioning
confidence: 99%